KEMAMPUAN MENULIS KREATIF PUISI DENGAN MENGGUNAKAN MEDIA GAMBAR SISWA KELAS VII SMP NEGERI 2 BONJOL KEBUPATEN PASAMAN - Safitri, Yelsi Delia; Laila, Aruna; Afrinda, Putri Dian (Pendidikan Bahasa Indonesia, 2013)
This research aims to describe the studentâs ability of class VII SMP N 2 Bonjol in writing poetry. This problem choose to catch the ability of student and to know the level of the studentâs ability in writing poetry seeing by the aspects of the use of figure speech, the use of imagery and use of diction. The discussion of this poetry choosen because the studentâs do not understand how to develop the elements of poetry. In addition less precise method used by the teacher in learning especially in learning to write poetry is not appropriate.This type of researchÂ  is quantitative with descriptive method. This research uses picture media. The used theory is about learning writing from Suyatno, with aims to studentâs can write fastly based on the picture is viewed. The population of this research is the studentâs of class VII SMP N 2 Bonjol, even the samples are studentâs class VII.1 and class VII.2 with amounts to 50 people with purposive sampling technique. This research data is poetry text written by the studentâs based on the three aspects these are the use of figure of speech, the use of imagery, and the use of diction.Based on the analysis of the data show that the ability in writing creative poetry using picture media class VII SMP N 2 Bonjol Pasaman regency are in over enough of analification (from the count average 68%) with details (a) the use of figure of speech classified nearly enough with the level of control 48%, (b) the use of imagery classified very good with the level of control 87,2%, (c) the use of diction more than enough with the level of control 71%. Based on data analysis above it can be concluded that the ability in writing creative poetry using picture media of studentâs class VII SMP N 2 Bonjol Pasaman regency is in more than enough analification with the level of control 68%.